(untitled) (Urdimento, 2024)
The essay seeks to return to the characterization of contemporary theater as “postdramatic”, according to Hans-Thies Lehmann, but reinforcing it with a consideration of drama as the ideological core of contemporary capitalism, and finally going beyond the ideas of the German theorist to propose a strong and critical concept of the postdramatic.